WELL BEING AT WORK:WHAT MAKES A DIFFERENCE? - Dirzyte, Aiste (European Scientific Journal, ESJ, 2014)
The article analyses current research trends on psychological constructs related to well being at work. Right around the turn of the last century, the field of psychology began to place greater importance on investigation what contributes to human flourishing, however, positive approach is still developing, and evidence on relationship between positive constructs has not been grounded culturally yet. This paper presents some results of the survey (n=197) which was conducted in Lithuania. It aimed to identify psychological factors that were found to be related to well being at work: job satisfaction, organizational commitment, psychological capital, personality traits, constructive thinking. This study confirmed that job satisfaction, organizational commitment and positive psychological capital are related constructs, and this Lithuanian research complements the previous studies done in various countries. The study has also demonstrated some statistically significant relations between personality traits and constructive thinking in Lithuanian organizations.